2015
DOI: 10.1111/1750-3841.12951
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of Organophosphorus Pesticides during Camellia Oil Production

Abstract: The purpose of this study was to investigate the fate of organophosphorus pesticides (OPs) during camellia oil production process, from camellia fruit to the final oil product. The results showed that the OPs were mainly distributed in the peel of camellia fruit, basically above 40% after the pesticide application of 7 d (P < 0.05). A small amount of OPs could enter into the seed and convert to crude camellia oil, with the concentration of 19.5 to 548.2 mg/L. In addition, metabolites of OPs (25.7 to 768.9 mg/L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Crude oil is needed to transform to odorless, bland and oxidative stable edible oil through the refining process, which is preferable to the consumer (Kim and Choe ; Farhoosh and others ; Liu and others ). The valuable bioactive compounds might easily degrade during the refining process due to the high temperature applied (Škevin and others ; Wei and others ).…”
Section: Introductionmentioning
confidence: 99%
“…Crude oil is needed to transform to odorless, bland and oxidative stable edible oil through the refining process, which is preferable to the consumer (Kim and Choe ; Farhoosh and others ; Liu and others ). The valuable bioactive compounds might easily degrade during the refining process due to the high temperature applied (Škevin and others ; Wei and others ).…”
Section: Introductionmentioning
confidence: 99%
“…Abd-Alrahman investigated the residue and dissipation kinetics of thiamethoxam in potato plants and soil in a field ecosystem. Some researchers have reported on the effects of handling and processing pesticide residues in raw cucumber, button crimini, olive oil, and camellia oil . There are recent studies of the effect of tea brewing conditions on pesticide residues in herbal tea and tea. These studies found several critical controlling factors, such as tea variety, tea/water ratio, tea brewing time, and washed or unwashed tea.…”
Section: Introductionmentioning
confidence: 99%